The study of mathematical equilibrium moisture content models (EMC) for Pisang Mas banana - Musikachai, Thawan-oranan; Tirawanichakul, Supawan; TIRAWANICHAKUL, YUTTHANA (Naresuan University Engineering Journal, 2018)
The main objective of this research was to evaluate the equilibrium moisture content (EMC) of Pisang Mas banana by static method among surrounding temperature between 45 and 65°C correlated to relative humidity (RH) of 0.11-0.86. And the experimental data were analyzed and simulated by 9 mathematical EMC models (Oswin, GAB, Chung-Pfost, Cauric, Kuhn, Smith, White and Eiring, Modified Smith and Modified Oswin). From the experimental results, they showed that at fixed surrounding temperature the EMC value of the bananas was non-linearly related to the surrounding relative humidity. Moreover at constant RH value the EMC value of the banana was inversely proportional to the surrounding temperature. Due to mathematical EMC model simulation, the criteria decision for getting the most suitable EMC model was determined by the highest coefficient of determination value (R2), the lowest value of root mean square error (RMSE), sum of squared error (SSE) and Chi square (c2). The simulation results stated that the predicted EMC data of GAB model was the best fitting to the experimental EMC data. And finally this simulated GAB model can apply to determine the EMC of Pisang Mas banana in tropical surrounding temperature and relative humidity for maintain quality of shelf life Keywords : Pisang Mas banana, Evaluation of Equilibrium Moisture Content, Mathematical models, Static method